Introduction to special issue on 'authoritarian neoliberalism'. (April 2019) - Fabry, Adam; Sandbeck, Sune
This article introduces readers to the special issue on 'authoritarian neoliberalism'. It charts the origins of the concept and summarizes the central arguments of the individual contributions to the special issue.